FORMULATION OF NANOCURCUMIN USING LOW VISCOSITY CHITOSAN POLYMER AND ITS CELLULAR UPTAKE STUDY INTO T47D CELLS - Chabib, Lutfi; Martien, Ronny; Ismail, Hilda (Indonesian Journal of Pharmacy, 2012)
Using  of  curcumin  as  anti  cancer  agent  is  restricted  by  its low  solubility,  therefore  it  has  low  bioavability.  This  obstacle  can be  solved  by  the  development  of  curcumin  nanoparticle. Nanoparticle  technology  has  been  started  to  be  developed  as  an alternative  solution to  improve drug  delivery pofile, especially  for the less bio-available chemical. This study was aimed to develope nanocurcumin  formulation  with  low  viscosity  chitosan  as  the matrix  and  to  study  its  ability  to  be  taken  into  the cells in  vitro. Method  used  in  the  formulation  of  nanocurcumin  in  this  study  is by ionic gelation followed by freeze drying. Entrapment  Efficiency then  assayed,  and  its  stability  was  tested  by  incubating  the formula  into  artificial  intestinal  fluid  (AIF).  Furthermore,  its toxicity  was  evaluated,  also  its  cellular  uptake  ability  into  T47D cell  line.  It  was  found  that  the  Entrapment  Efficiency  in  acetate buffer  at  pH  4  is  higher  than  at  pH  5.  This  formula  also  has  a good  stability  in  AIF.  For  the  cellular  uptake  study  through fluorescence  microscope,  it  was  found  that  the  complex  has  an ability  to  penetrate  cellular  membrane  into  the  cytosol.  The cytotoxicity  study  tell  us  that  the  nanocurcumin  is  non-toxic  to normal  cell line. For  the characterization of the nanoparticles, the average  size  of  this  particle  is  269.8  nm,  its  zeta-potential  is +18.63 mV, with spherical particle morphology. From the result ofthis study, it is concluded that formulation of nanocurcumin using low viscosity chitosan polymer as the matrix has a great potential as an alternative for anticancer therapy.Key words: nanoparticle, curcumin, low viscosity chitosan, T47D cell line.